Political Institutions, ICT Infrastructure, and Social Networks Impact on Citizens ’ Policy Formulation E-participation Engagement Behaviour in Uganda - Nabafu, Robinah; Moya, Musa Bukoma; Kituyi, Geoffrey Mayoka (University of Dar es Salaam Library Journal, 2023)
This paper assessed the impact of political institutions, ICT infrastructure, and social networks on citizens ' self-motivation and engagement in policy formulation. The study was motivated by limited citizen engagement in policy formulation in Uganda which has made Uganda as a country to score poorly both in the e-government and e-participation index and contradict Article 38 of the Constitution of Uganda which advocates for citizen engagement in policy formulation. Thus, this study aimed to increase citizen engagement through the adaption of the Motivation, Opportunity, and Ability (MOA) model. A survey collected Primary data from 361 village health teams and local council Chairpersons. The collected data was analysed using SPSS and SEM. Results found that; political institutions, ICT infrastructure, and social networks influence self-motivation, political institutions, and self-motivation influence engagement while self-motivation fully mediates the relationship between ICT infrastructure, social networks, and citizen engagement, it partially mediates the relationship between political institutions and engagement. The practical implication is that political institutions are essential in stimulating citizens ' self-motivation and engagement.